Revision of Bryconamericus (Characiformes, Characidae) from Pacific coastal and Amazon River drainages with descriptions of three new species: Revision of Bryconamericus characid fish (Revista de Investigaciones Universidad del Quindío, 2023)
We report the results of a taxonomic revision of the species of Bryconamericus from the Amazon River Basin of Peru, Ecuador, Bolivia and the Pacific coastal rivers of Peru. Based on morphological analyses, four valid species are recognized: B. bolivianus Pearson 1924, B. osgoodi Eigenmann & Allen 1942, B. pachacuti Eigenmann 1927 and B. phoenicopterus (Cope 1872). Three new species are described: B. lambayequensis sp. n. from the Cañariaco River, Pacific coast, Peru and two from the Amazon River Basin: B. abalio sp. n. from the Ucayali River drainage, Peru, and B. parapetiensis sp. n. from Itenez/Parapeti, Amazonia, Bolivia. Two species are synonymized and one was recently assigned to another genus: Bryconamericus alfredae is considered a junior synonym of Acrobrycon ipanquianus; Bryconamericus grosvenori is a junior synonym of B. bolivianus. A taxonomic key to these species of Bryconamericus and comments on the conservation status of the Amazonian and Pacific coast freshwater ichthyofauna are also included.
Keywords: Diversity; neotropical fish; morphology; melanophores; taxonomy